Comparison of Several Types of Plasma as Media in the Germ Tube Test for Identification of Candida Albicans - Yunia Hidayati; Asnaily Asnaily; Akhirul Jumaisal; James Perdinan Simanjuntak (Jurnal Teknokes, 2023)
Candida albicans is a commensal on the oral mucosal surfaces of healthy individuals but can be pathogenic in immunocompromised individuals. The germ tube test is an inexpensive, faster, and easier method used to identify and differentiate it from other yeast species. Generally, the test is carried out using serum as the medium. Plasma overall has the same characteristics as serum and differs only in the content of clotting factors. In addition, plasma is easier to obtain than serum in most healthcare services. This study aims to demonstrate three types of plasma as alternative media for germ tube test. CPDA (Citrate Phosphate Dextrose Adenine), EDTA (Ethylenediaminetetraacetic), and Sodium Citrate plasma were compared to serum in producing of germ tubes. Each plasma and serum was tested in five repetitions. The experimental method was carried out in Mycology Laboratory at Health Polytechnic of Jambi. The data were observed based on the germ tube formation time and analyzed with one-way ANOVA test. The result showed the lengths of germ tube formation time were significantly different. Although CPDA plasma was also significantly different compared to serum, it showed the average time which is at the minimum limit of the incubation time range that is recommended in the standard protocol of the test. This study concluded that plasma can be used as a substitute for serum in the germ tube tes, especially CPDA plasma, as it is faster in formating time, easier to obtain, and considered safer to use than others.